SYNTHESIS OF NANOFIBER MEMBRANE BY ELECTROSPINNING TECHNIQUE - (:unkn) unknown (JOHN WILEY & SONS INC, 2014)
Novel imidazole functionalized mesoporous poly (vinyl alcohol) (PVA)/SiO2, PVA/SiO2 organic-inorganic hybrid nanofiber membranes and pure PVA nanofiber membranes were synthesized by electrospinning combined with UV-curable system. PVA and Geniosil XL 33 (as a SiO2 source) were mixed with N-Vinyl Imidazole (NVI) to prepare the nanofiber polymer solution. To obtain nanofiber membrane, a strong electrostatic force by a high static voltage was applied to the polymer solution by exposuring to UV radiation at the same time. The experimental parameters such as voltage, flow rate, distance from syringe-tip to the collector were optimized. The synthesized membranes were characterized by Fourier-transform infrared spectroscopy (FTIR). Nanofiber diameter and surface area were measured by scanning electron microscopy (SEM) and Brunauer-Emmert-Teller (BET) analysis, respectively. Thermal property of membranes was examined by Thermogravimetric-Differential Thermal Analysis (TG-DTA).
Keywords: Nanofiber; Electrospinning; Hybrid material